The Symbolic Meaning of Kuadai Dance Performance in the Society of Semende Lampung - Saputri, Amelia Hani; Hartono, Hartono; Florentinus, Totok Sumaryanto (Universitas Negeri Semarang, 2018)
Kudai dance as a medium of collective expression of Semendesociety is identical with the women strength as the source of life. In the aspect of its performance, It contains social interaction through the symbols that is expressed through the aesthetics of the female body.The purpose of the article is to explain the symbolic meaning of Kuadai dance performance expressed by Semende society in Lampung.This research used qualitative method with interdisciplinary approach. The data collection used the technique of observation, interview, and documentation. The data validity was based on the credibility criteria with triangulation technique. The data analysis used the procedure of dance research by Gertrude Prokosch Kurath that is focused on dance analysis especially on symbol and meaning in Kuadai dance. The results showed that Kuadaidance is a form of tradition reality imitation which exists among Semendesociety as an agrarian society that outs forward the tradition of tunggu tubang (the first daughter as a shelter and a manager of family’s treasure. The personality of tunggu tubang that is full of patience, consistence, and responsibility is manifested through the Kuadai dance movements.The plate as property is a symbol of a respect as well as a representation of a woman that should be treated gently, carefully, lovingly, and with sacred. The dominant floor pattern symbolizes the Semende society that always respects the customs’ regulation. The dance accompaniment with slow tempo symbolizes Semende society that is full of tranquility and togetherness.